Categorization of Chinese Character Radicals and Instruction of Chinese Character for Teaching Chinese as Foreign Language - Jinming, Cui (Sinología hispánica. China Studies Review, 2017)
Chinese characters have always been the difficulty of teaching Chinese as a foreign language, especially for Chinese learners of non-Chinese cultural circles. Based on the characteristics of Chinese characters and the cognitive law of "linguistic concept" and "categorization" of Chinese characters, the article aims to design a set of radicals "Typical attribute", with the radicals as the "prototype", "typical members" and "atypical members" of the hierarchical system for Chinese learners more systematic and more reasonable to master the Chinese characters to provide a teaching model, and After the teaching of Chinese characters to provide some reference.